2016
DOI: 10.1088/1361-6439/27/2/025004
|View full text |Cite
|
Sign up to set email alerts
|

Microelectromechanical system-based electrochemical seismic sensors with an anode and a cathode integrated on one chip

Abstract: This paper presents a microelectromechanical system (MEMS)-based electrochemical seismic sensor with an anode and a cathode integrated on a single chip. The proposed approach decreases the number of requested wafers as the sensing unit from seven to two. In addition, no alignment and no bonding among the electrodes are needed, significantly simplifying the fabrication process. The experimental results indicate that the proposed device produced a sensitivity of 5771.7 V (m s−1)−1 at 1.4 Hz and a noise level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In order to address these issues, He et al and Deng et al fabricated sensitive electrodes based on microfabrication. Although high-consistency sensitive electrodes were manufactured, multiple wafers were required and they cannot be properly aligned [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to address these issues, He et al and Deng et al fabricated sensitive electrodes based on microfabrication. Although high-consistency sensitive electrodes were manufactured, multiple wafers were required and they cannot be properly aligned [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…He et al reported sensing units where several microfabricated layers of electrodes and insulation were stacked together, and due to poor alignment accuracies, the reported electrochemical microseismometers suffered from the key issue of low consistencies [20]. In order to reduce the challenges in manufacture and assembly, Deng et al and Huang et al, based on different methods of fabrication, developed sensing units with integrated anodes and cathodes [21][22][23]. Nevertheless, since two chips still needed to be manually aligned and assembled, they still suffered from poor consistencies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the introduction of MEMS technologies, the performances of the sensitive electrodes of electrochemical seismic sensors were greatly improved [ 7 , 8 , 9 , 10 , 11 ], which attracted increasingly more interests from researchers all over the world.…”
Section: Introductionmentioning
confidence: 99%